Virtual Reality Technology for Learning the Process of Organic Rice Cultivation - Kunlerd, Attapol (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 3 (2022): July-September 2022DO - 10.14456/nujst.2022.27, 2021)
Organic rice cultivation is a process that requires skilled personnel. Therefore, those who have begun to study must learn from those who have direct experience through training. However, with the problem of organizing training requires a lot of location and operating costs; the idea is to apply Virtual Reality technology that helps to create a learning environment to solve problems. The objective of this research is the following: 1) develop virtual reality technology on learning to plant organic rice 2) study the users’ satisfaction of the virtual reality technology system. In which the study population was farmers in Surin Province. A sample of 400 people was used by the convenient sampling method. The research tools included 1) virtual reality technology on learning about organic rice cultivation 2) satisfaction questionnaire. The statistics used in this research were mean and standard deviation. The tools were tested with sample group in conjunction with agricultural training and published through social media by collecting research data during August - September 2020. The result of research showed that 1) to be able to develop Virtual Reality technology in the form of a video that can be viewed in 360 degrees by distributing through social media via mobile applications and websites. The content shows the process of growing organic rice which consists of a total of 11 scenes. 2) The result of the satisfaction assessment showed that the samples were able to access the information easily and quickly, easier to understand the process of planting organic rice and apply the knowledge into practice by oneself. The overall satisfaction assessment results were standard deviation was 0.13 and the mean was 4.34 which can be implied to be at the high level. Keywords: Virtual reality in rice planting, Organic rice, Virtual reality